A new integrative approach to assess aortic stenosis burden and predict objective functional improvement after TAVR - de la Torre Hernandez, Jose M.; Veiga Fernandez, Gabriela; Ben-Assa, Eyal; Sainz Laso, Fermin; Lee, Dae-Hyun; Ruisanchez Villar, Cristina; Lerena, Piedad; Garcia Camarero, Tamara; Cuesta Cosgaya, Jose M.; Fradejas-Sastre, Victor; Benito, Mercedes; Barrera, Sergio; et al. (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND A non-negligible proportion of patients who undergo transcatheter aortic valve replacement (TAVR) do not report any symptomatic improvement or even die in the short-mid term. We sought to assess the degree of objective functional recovery after TAVR, its prognostic implications and to develop a predictive model. METHODS In a cohort of patients undergoing TAVR a prospective evaluation of clinical, anatomical and physiological parameters was conducted before and after procedure. These parameters were derived from echocardiography, non-invasive analysis of arterial pulse wave and cardiac tomography. Objective functional improvement 6 months after TAVR was assessed using 6-minute walk test and NT-proBNP levels. The derived predictive model was prospectively validated in a different cohort. Clinical follow-up was conducted at 2 years. RESULTS Among the 212 patients included, objective functional improvement was observed in 169 patients (80%) and subjective in 187 (88%). Patients with objective functional improvement showed a much lower death rate at 2 years (9% vs 31% p=0.0002). Independent predictors of improvement were mean aortic gradient ≥40 mmHg, augmentation index75 ≥45%, posterior wall thickness ≤12 mm, and absence of atrial fibrillation. A simple integer-based point score was developed (GAPA score) which showed an area under the curve of 0.81 for the overall cohort and 0.78 for the low-gradient subgroup. In a validation cohort of 216 patients these values were 0.75 and 0.76 respectively. CONCLUSIONS A 80% of patients experienced objective functional improvement after TAVR, showing a significantly lower 2-year mortality rate. A predictive score was built which showed a good discriminative performance in overall and low-gradient populations.